REALIZING DEMOCRATIC EDUCATION THROUGH THE DEVELOPMENT OF PESANTREN EDUCATION PROCESS - Muh. Nur Rochim Maksum; Deddy Ramdhani; Meti Fatimah; Athia Tamyizatun Nisa (Profetika: Jurnal Studi Islam, 2021)
An educational institution will be able to actualize democratic education in its school environment holistically as described by Zamroni (2011)  must at least integrate three important elements in a school. The three elements are the structure, the culture of the school, and the educational process carried out by teachers. Previous literature studies show that the integration of the three elements has not been maximally actualized in educational institutions. This research will explain the actualization of democratic education through the reorientation of the democratic education process through the development of extracurricular activities of modern Islamic boarding school Assalaam Surakarta Indonesia. To achieve the research objectives, this study uses a qualitative approach with three data collection techniques: interviews, documentation, observations. The results of this study show that the actualization of democratic education in the boarding school environment through the development of extracurricular activities can be done by reorienting extracurricular activities. At least the reorientation process can be carried out in the early stages, namely, the use of extracurricular activities proportionately and professionally, to carry out the management of the extracurricular based on democratic values and develop extracurricular activities in a structured and planned manner to develop democratic values gradually and continuously.